2015
DOI: 10.1111/1755-0998.12474
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcodes from century‐old type specimens using next‐generation sequencing

Abstract: Type specimens have high scientific importance because they provide the only certain connection between the application of a Linnean name and a physical specimen. Many other individuals may have been identified as a particular species, but their linkage to the taxon concept is inferential. Because type specimens are often more than a century old and have experienced conditions unfavourable for DNA preservation, success in sequence recovery has been uncertain. This study addresses this challenge by employing ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
152
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 134 publications
(156 citation statements)
references
References 38 publications
4
152
0
Order By: Relevance
“…There was 100% concordance between sequences generated from the same specimen using NGS and Sanger sequencing for the 20 type specimens examined by Prosser et al (2016). Our extended data set (93 type specimens) confirms this result.…”
Section: Quality Control Sanger Sequencing Versus Ngssupporting
confidence: 74%
See 4 more Smart Citations
“…There was 100% concordance between sequences generated from the same specimen using NGS and Sanger sequencing for the 20 type specimens examined by Prosser et al (2016). Our extended data set (93 type specimens) confirms this result.…”
Section: Quality Control Sanger Sequencing Versus Ngssupporting
confidence: 74%
“…For the geometrid types from NHM London, the quality control of the sequences which were generated in parallel from the same DNA extracts with the Sanger approach and with NGS revealed a 100% match in all cases (Prosser et al 2016). The same study showed that all DNA sequences from century-old type specimens perfectly matched (100%) sequences from recently collected specimens when these were available in the Barcode of Life Data Systems, BOLD (Ratnasingham and Hebert 2007).…”
Section: Dna Analysismentioning
confidence: 87%
See 3 more Smart Citations